Diseño de un modelo de costos ABC para la empresa Concentrado Elite SAS (2021)
This document relates to the development of an ABC cost model for the company Concentrados Elite S.A.S. in order to know the real cost of production in each product line based on activities that are carried out in the production and administrative process for decision making.